PARTIAL LEAST SQUARE: PENGARUH FLEKSIBILITAS TERHADAP KEPUASAN DAN LOYALITAS - Nina Valentika; Vivi Iswanti Nursyirwan (Jurnal Ilmiah Econosains, 2020)
This study aims to examine the direct effect of flexibility on customer satisfaction, the direct effect of flexibility on customer loyalty, the direct effect of customer satisfaction on customer loyalty and examine the indirect effect of flexibility on customer loyalty with customer satisfaction as an intervening variable. The method used in selecting respondents is the purposive sampling method with a total of 100 respondents. Respondents in this study were students of the Faculty of Economics, Department of Accounting who were also Shopee users and had shopped at least once. The research model uses Structural Equation Modeling Partial Least Square (SEM-PLS). From these studies, it can be found that flexibility has a significant positive effect on customer satisfaction at the 10% level. Flexibility has a significant positive effect on loyalty at the 10% level. Customer satisfaction has a significant positive effect on loyalty at the 10% level. There is a significant positive indirect effect between flexibility on loyalty and customer satisfaction as an intervening variable at the 10% level.